2015
DOI: 10.1039/c5cp02620b
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the photothermal efficiency of gold nanoparticles using tryptophan as an in situ fluorescent thermometer

Abstract: The photothermal efficiencies, denoting the efficiency of transducing incident light to heat, of gold nanoparticles of different diameters (∅ = 22-86 nm) were quantified upon exposure at 532 nm. The fluorescence of tryptophan at 300-450 nm upon 280 nm excitation serves as an in situ fluorescent thermometer to illustrate the evolution of the average temperature change in the heating volume of the nanoparticle solution. The fluorescence intensity decreases as the temperature increases, having a linear gradient o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 49 publications
2
23
0
Order By: Relevance
“…The size and morphology of Au NPs were two key factors for the photothermal conversion. 38 Here, we synthesized Au NPs with different sizes by a seeding growth method. The diameter effect of Au NPs on the photothermal conversion efficiency was studied using three accessible and reproducible methods through monitoring the changes of temperature, the vapor pressure and mass loss of the nanouids.…”
Section: Introductionmentioning
confidence: 99%
“…The size and morphology of Au NPs were two key factors for the photothermal conversion. 38 Here, we synthesized Au NPs with different sizes by a seeding growth method. The diameter effect of Au NPs on the photothermal conversion efficiency was studied using three accessible and reproducible methods through monitoring the changes of temperature, the vapor pressure and mass loss of the nanouids.…”
Section: Introductionmentioning
confidence: 99%
“…Optical methods based on temperature-sensitive probes are an appealing alternative. Organic dyes, rare-earth doped (nano)­crystals, or quantum dots may be used to report temperature through changes in their spectrum, intensity, lifetime, or anisotropy. , SERS also allows for temperature determination by monitoring the anti-Stokes to Stokes ratio for molecules in the vicinity of NPs, although suffering from weak signals, low photostability, and hard to calibrate wavelength-dependent plasmon-enhanced cross sections that make implementations difficult at the single-NP level. , Yet another optical method relies on determining the temperature from variations in the refractive index . However, retrieving accurate temperature measurements of plasmonic NPs using these methods is not always possible.…”
mentioning
confidence: 99%
“…The photothermal abilities of nanostructures are determined by the quantity of strongly absorbed incident light and resonant energy efficiently converted into heat energy; thus, most studies have experimentally or computationally investigated the photothermal conversion efficiency (PTCE) defined by the ratio of the heat generation to laser power loss or the ratio of absorption to extinction coefficient by varying the nanostructure size and shape. Jiang et al and Chiu et al found that the PTCE increases as the diameter of the gold nanoparticles (GNPs) decreases under a 532 nm continuous‐wave illumination . Guo et al investigated the PTCE for solar steam generation under solar illumination by measuring the temperature change, vapor pressure, and mass loss of nanofluids .…”
Section: Introductionmentioning
confidence: 99%
“…Jiang et al and Chiu et al found that the PTCE increases as the diameter of the gold nanoparticles (GNPs) decreases under a 532 nm continuous-wave illumination. [17,18] Guo et al investigated the PTCE for solar steam generation under solar illumination by measuring the temperature change, vapor pressure, and mass loss of nanofluids. [9] In the case of anisotropic nanostructures, Mackey et al reported that the optimum size of gold nanorods (GNRs) is 28 nm in length and 8 nm in width considering the PTCE, electric field, and distance between the particles.…”
Section: Introductionmentioning
confidence: 99%